(untitled) (Faridpur Medical College Journal, 2025)
Premature rupture of membrane is the rupture of gestational membranes prior to the onset of labor. When membrane rupture occurs before 37 weeks of gestation, it is referred to as preterm premature rupture of membrane. Gestational diabetes mellitus and diabetes in pregnancy probably increase the risk of premature rupture of membrane or prevalence of premature rupture of membrane and fetal complications during pregnancy. This descriptive cross sectional study was done in Fetomaternal Medicine Unit of Dhaka Medical College Hospital from 01/01/2020 to 31/12/2020 to find out the number of gestational diabetes mellitus and diabetes in pregnancy among all admitted patients of preterm premature rupture of membrane. A total of 103 patients with preterm premature rupture of membrane were admitted. Among them10 (9.7%) participants were suffering from gestational diabetes mellitus and diabetes in pregnancy, 6 (5.8%) were multiple gestation, 7 (6.7%) were associated with preterm labor, 7 (6.79%) patients had gestational hypertension, 4 (3.88%) were with fetal growth restriction, 3 (2.91%) had fetus with congenital anomaly and 2(1.94%) patients were with anaemia. Out of 103 participants, total study showed that gestational diabetes mellitus and diabetes in pregnancy are most common risk factors of preterm premature rupture of membrane. Faridpur Med. Coll. J. 2025;20(2):35-38